Composite Materials in Design Processes - Minak, Giangiacomo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The use of composite materials in the design process allows one to tailer a component's mechanical properties, thus reducing its overall weight. On the one hand, the possible combinations of matrices, reinforcements, and technologies provides more options to the designer. On the other hand, it increases the fields that need to be investigated in order to obtain all the information requested for a safe design. This Applied Sciences Special Issue, "Composite Materials in Design Processes", collects recent advances in the design methods for components made of composites and composite material properties at a laminate level or using a multi-scale approach.